Holter Electrocardiography Findings and P‐Wave Dispersion in Pediatric Patients with Transcatheter Closure of Atrial Septal Defects. Issue 2 (8th October 2013) - Ozyilmaz, Isa; Ozyilmaz, Sinem; Tola, Hasan Tahsin; Saygi, Murat; Kiplapinar, Neslihan; Tanıdır, Cansaran; Ergul, Yakup; Guzeltas, Alper; Odemis, Ender
<x xml:space="preserve">Abstract</x> Background This study aimed to determine the frequency of postintervention arrhythmia and factors associated with the development of arrhythmia, including the correlation between arrhythmia and P‐wave dispersion, and the effects of the latter on transcatheter closure of atrial septal defects (ASDs). Methods Holter ECG recordings were performed before and after the intervention and 6 and 12 months later in 47 of the 59 patients who had undergone transcatheter ASD closure and once in the healthy control subjects. Results A statistically significant correlation was identified between the patients' arrhythmia grade according to Lown's system and each of the following: the number of defects, the size of the atrioventricular valve rim, the presence of an atrial septal aneurysm. Conclusion The frequency of arrhythmia increases after transcatheter ASD closure, gradually decreases within the next year, and is most frequently of a benign nature. Lown's arrhythmia grading of patients occluded with either the Amplatzer septal occluder (ASO) or the Cardio‐O‐Fix septal occluder (CSO) were compared, and the arrhythmia frequency was higher with the latter. One day after the intervention, the P maximum (Pmax) and the P dispersion(Pdis) values were not increased but in fact slightly reduced in patients occluded with either ASO or CSO. An improvement in the electrical system resulting from early anatomical and mechanical healing following transcatheter ASD occlusion may explain the reduction in the Pmax and Pdis values.